2019
DOI: 10.18632/oncotarget.27098
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative, pro-inflammatory, and angiogenesis regulator gene expression profile defines prognosis in different histopathological subtypes of nodal peripheral T-cell lymphoma

Abstract: Nodal peripheral T-cell lymphoma (PTCL) is an aggressive and heterogeneous malignancy with poor prognosis. We studied the prognostic impact of the expression profile of genes related to cell proliferation ( CCNA2 , TOP2A , and CHEK1 ), pro-inflammatory activity ( NFkB1 and IKBkB ), and angiogenesis ( VEGF1 ) in nodal PTCL outcomes, as well as the ability of this genomic pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The first subgroup of cells (clusters 3, 5, 7, and 8) was highly proliferative and was labeled with MKI67 , [25] TOP2A , [26] and CDK1 genes [27] . According to GO and KEGG analysis of the DEGs in every cluster, this group of cells could be further divided into 2 subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…The first subgroup of cells (clusters 3, 5, 7, and 8) was highly proliferative and was labeled with MKI67 , [25] TOP2A , [26] and CDK1 genes [27] . According to GO and KEGG analysis of the DEGs in every cluster, this group of cells could be further divided into 2 subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that overexpression of CCNA2 gene and CHECK1 protein were associated with poor prognosis in nPTCLs [12]. Here, we aimed to test and confirm the hypothesis that GATA3 gene expression would be associated with overall survival and progression-free survival and could be used as a marker to differentiate histopathological subtypes of nPTCLs.…”
Section: Introductionmentioning
confidence: 89%